Investigations of Corruption in Police Resort of Pati - Miftah Anshori (Jurnal Daulat Hukum, 2018)
Corruption is an extraordinary crime, the State Police as a law enforcement tool, have a responsibility in combating corruption is to conduct the investigation of corruption. This study aims to determine: a. What obstacles facing investigators in conducting investigations and inquiries Corruption in Police Resort Pati, and b. Any solution to the obstacles faced by investigators in the investigation and investigation of corruption in the Police Resort Pati. Methods of research in this thesis with empirical sociological juridical approach, which examined the relevant legal principles of the regulatory relationship with the other regulations as well as the relation to the application in practice, in addition to analytic descriptive approach illustrates the investigation of Police against corruption. The results of the study concludes: a) Obstacles in the investigation process of Corruption today were related to the internal policy of the State Attorney Pati would only accept Corruption Case Files of Investigator with the calculation of financial loss State of BPK, that since the issuance of SEMA No. 04 / Bua.6 / Hs / SP / XII / 2016 dated December 9, 2016, which describes the authorized institutions stating financial loss State is the CPC; b) Solution for make problem solving on the problems the invertigator in the former of inverstigation coordinated directly with BPK, because the terms of demand of state loss on BPK the status of the case is invertigations. Keywords: Investigation; Police; Corruption.